Authority in Ocean Governance Architecture - Mondré, Aletta (2022)
In this article, we demonstrate that the ocean is a space of politics and explore the what, who, and how of ocean governance. We first sketch the governance architecture and examine challenges and shortcomings concerning political authority. Starting from a definition of “ocean governance,” we highlight that two fundamentally different regulatory approaches are applied to the ocean: a spatial ordering on the one hand and a sectoral segmentation on the other. States are the central actors regulating the use and protection of marine areas, but state sovereignty is stratified, with diminishing degrees of authority farther from the shoreline. As vast marine spaces are beyond the exclusive control of any given territorial state, political authority beyond areas of national jurisdiction must first be created to enable collective decision-making. Consequently, a multitude of authorities regulate human activities in the ocean, producing overlaps, conflicting policies, and gaps. Based on recent contributions to the fast-growing ocean governance research field, we provide a thematic overview structured along the dimensions of maritime security, protection of the marine environment, and economics to unveil patterns of authority in ocean governance.